2009
DOI: 10.1166/jnn.2009.gr05
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Water-Insoluble Drugs in Poly(butyl cyanoacrylate) Nanoparticles

Abstract: Hydrophobic drugs, loperamide and paclitaxel, were loaded in poly(butyl cyanoacrylate) nanoparticles by polymerization of n-butyl-2-cyanoacrylate in aqueous-organic media in the presence of a drug. The particles were stabilized by dextran 70,000 and poloxamer 188 or by 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-5000] sodium salt. It was shown that in the presence of dichloromethane, methanol or ethanol the encapsulation efficiency of loperamide in the nanoparticles reached 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous reports have demonstrated that reduction of particle size, amorphous transformations, and intermolecular hydrogen-bond formation all effectively increase the encapsulation efficiency of drugs and further enhance their drug release. , Encapsulation efficiency is a factor to evaluate drug release from pharmaceutical formulations, such as liposomes, microspheres, and nanoparticles . Additionally, Mora-Huertas et al have reported that the method of nanoparticle preparation and the choice of polymer were the major factors affecting the success of nanoparticle formulations on the drug release …”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have demonstrated that reduction of particle size, amorphous transformations, and intermolecular hydrogen-bond formation all effectively increase the encapsulation efficiency of drugs and further enhance their drug release. , Encapsulation efficiency is a factor to evaluate drug release from pharmaceutical formulations, such as liposomes, microspheres, and nanoparticles . Additionally, Mora-Huertas et al have reported that the method of nanoparticle preparation and the choice of polymer were the major factors affecting the success of nanoparticle formulations on the drug release …”
Section: Resultsmentioning
confidence: 99%
“…[367] Interestingly, it was found that the efficacy of the surfactants could vary depending upon the type of NP used. In analogous experiments conducted with poly(butyl cyanoacrylate) (PBCA) NPs (discussed in greater detail below), both PS 80 and poloxamer 188 induced similar, distinctive pharmacological effects when delivering loperamide [368,369] and doxorubicin [370,371] across the BBB (i.e. both surfactants were effective).…”
Section: Nanospheres and Nanocapsulesmentioning
confidence: 99%
“…Reports have been available describing the preparation of paclitaxel-loaded PBCA nanoparticles by mini-emulsion methods or anionic polymerization (15,29), but the ability of these nanoparticles to overcome P-gp-mediated MDR has not been investigated. In the current study, we prepared a paclitaxel-loaded PBCA nanoparticles using interfacial polymerization and examined their ability to overcome P-gpmediated MDR in ovarian cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%